The Survival Benefits of Surgical Resection and Adjuvant Therapy for Patients With Brainstem Glioma - Liu, Zhuoyi; Feng, Songshan; Li, Jing; Cao, Hui; Huang, Jun; Fan, Fan; Cheng, Li; Liu, Zhixiong; Cheng, Quan (Frontiers in Oncology, 2021)
Abstract: Purpose: The role of surgical resection in the treatment of brainstem glioma (BSG) is poorly understood. For pediatric low-grade (LGBSG）group, several monocentric small-scale retrospective studies reported contradictory conclusions. And there was no clinical study focused on surgical resection for adult or pediatric high-grade (HG) patient groups. This study aims to illustrate whether surgical resection and adjuvant therapy provide survival benefits for patients with BSG. Patients and methods: This retrospective cohort study included 529 patients with histologically confirmed BSG in Surveillance Epidemiology and End Results (SEER) database from 2006-2015. Patients were divided into four groups by age and World Health Organization (WHO) grade. Univariate and multivariate analyses were conducted to determine the prognosis effects of surgical resection and adjuvant therapy on cancer specific survival (CSS). Kaplan-Meier curves of CSS were also plotted by different treatment options to compare the survival probability. All analyses were done in the entire cohort and four different groups separately. Results: The final sample included 529 patients. The entire study population was divided into groups of pediatric LG (n=251, 47.4%), pediatric HG (n=43, 8.1%), adult LG (n=189, 35.7%) and adult HG (n=46, 8.7%). Pediatric LGBSG group had the highest gross total resection (GTR) rate (61.4%) and 5-year CSS rate (89.3%). Multivariate analysis identified GTR as independently significant predictor for prolonged CSS in pediatric LGBSG group (HR0.58, 95%CI 0.39-0.87, P=0.01); Kaplan-Meier curves of pediatric LGBSG group confirmed that patients treated with GTR had significantly better survival probability (P=0.039). Multivariate analysis identified the combination of radiotherapy (RT) and chemotherapy (CT) as independently significant predictor for better CSS in adult HGBSG group (HR0.29, 95%CI 0.09-0.98, P<0.05). Kaplan-Meier curves of adult HGBSG group validated that patients treated with both RT and CT in adult HGBSG group had the best survival probability (P=0.043). Conclusion: Pediatric LGBSG group had the highest GTR rate and the most favorable clinical outcome. GTR can provide significant survival benefits for pediatric LGBSG group. Combination of RT and CT can provide significant survival benefits for adult HGBSG group.